POINT-TO-POINT MULTIPLE-GOAL TASK REALIZATION OF MANIPULATOR AND POSITIONING TABLE: A DESIGN OF AUXILIARY LINKAGES - Gueta, Lounell Bahoy; Chiba, Ryosuke; Arai, Tamio; Ueyama, Tsuyoshi; Rubrico, Jose Ildefonso Udang; Ota, Jun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
A task realization for a robot manipulator system with multiple goals is presented in this paper. A combination of design methods involving programming-based and hardware-based methods is employed in the task realization. In particular, auxiliary linkages are designed with reference to a tool attachment and a base placement. A tool attachment is a fixed linkage added at the manipulator end-effector, whereas a base placement is viewed as the design of a virtual linkage at the manipulator base. The design of auxiliary linkages optimizes the length of the tool attachment and the orientation of the tool (e.g., a camera held by a manipulator in an inspection task), as well as the manipulator base placement. Goal rearrangement and motion coordination methods are integrated for minimal-time task realization. Simulations are conducted to verify the effectiveness of the proposed method. The results show that an improvement of 14% can be achieved.